2017
DOI: 10.1002/pbc.26567
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for patients with pediatric cancer during inpatient acute care: A systematic review of literature

Abstract: Physical inactivity has been shown to exacerbate negative side effects experienced by pediatric patients undergoing cancer therapy. Exercise interventions are being created in response. This review summarizes current exercise intervention data in the inpatient pediatric oncology setting. Two independent reviewers collected literature from three databases, and analyzed data following the PRISMA statement for systematic reviews and meta-analyses. Ten studies were included, representing 204 patients. Good adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 23 publications
2
40
0
7
Order By: Relevance
“…Early literature on physical activity interventions for children during acute cancer treatment focused on exercise prescription strategies that address physical impairments 9,56 . More recently, promising examples of complex intervention design have emerged in the acute pediatric cancer setting, but more work needs to be done to ensure the strategies used are theoretically informed, feasible, and address factors beyond the child and family unit 18,43,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Early literature on physical activity interventions for children during acute cancer treatment focused on exercise prescription strategies that address physical impairments 9,56 . More recently, promising examples of complex intervention design have emerged in the acute pediatric cancer setting, but more work needs to be done to ensure the strategies used are theoretically informed, feasible, and address factors beyond the child and family unit 18,43,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings from exercise studies support the promotion of physical activity and use of exercise science principles to gain and maintain physiological, functional, and quality of life benefits during and after treatment for cancer . During treatment, the proposed benefits include improved physical functioning, body composition, immune and cardiorespiratory systems, sleep, energy, and health‐related quality of life . Integrating contents of physical education into hospital routine may also be important to promote physiologic motor development and maintain the normality (such as gym classes) that patients are missing.…”
Section: Introductionmentioning
confidence: 88%
“…6,7 During treatment, the proposed benefits include improved physical functioning, body composition, immune and cardiorespiratory systems, sleep, energy, and health-related quality of life. 8 Integrating contents of physical education into hospital routine may also be important to promote physiologic motor development and maintain the normality (such as gym classes) that patients are missing.…”
Section: General Benefits Of Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity levels and motor performance are dramatically reduced during and shortly after treatment [12][13][14][15] and such limita-tions persist throughout adulthood [5,6,[16][17][18][19]. There is no doubt that physical activity and sports interventions contribute to the reduction of late effects and influence clinical and psychosocial outcome positively [20][21][22][23]. However, our experience and a survey in one outpatient Clinic of Pediatric Oncology showed that the questioned children and adolescents with sarcoma are not attending school and are excluded from activities in sports clubs [24].…”
Section: Introductionmentioning
confidence: 99%